Occurrence And Types Of Interference In The Language - Avadır, Kamala Jafarova (Advances in Social Sciences Research Journal, 2017)
The article investigates the problem of interference in the language. As we know, a negative interaction of the learning of languages is most evident as interlingual interference. Such an impact makes itself most evident as influence of the features of the already learned language on the acquisition of a second one. That is why scientists who carry out studies in this field have shown that the learning of such a case is of a great practical importance. They concluded that the insertion of “foreign element” in a second language while learning it eliminated a barrier between the distinguishing features of both languages. These scientists think that in this case a new system arise in a bilingual’s conscience which can be regarded as “a third system”. Thus, distinguishing features of both a first and a second language are mixed in such a system.